2018
DOI: 10.1002/jmri.25952
|View full text |Cite
|
Sign up to set email alerts
|

1.0T MR‐guided percutaneous coaxial cutting needle biopsy in pancreatic lesion diagnosis

Abstract: 2 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2018;48:382-388.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The first MRI-guided clinical trials were reported in 1986 (13). Since then, MRI-guided clinical applications have been successfully applied to lesions in various anatomical regions, such as pancreatic, breast, prostate, lung tumor, and renal tumor lesions (14)(15)(16)(17)(18). After ∼20 years of clinical use, MRIguided breast biopsy has evolved into a routine method in Western European countries (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The first MRI-guided clinical trials were reported in 1986 (13). Since then, MRI-guided clinical applications have been successfully applied to lesions in various anatomical regions, such as pancreatic, breast, prostate, lung tumor, and renal tumor lesions (14)(15)(16)(17)(18). After ∼20 years of clinical use, MRIguided breast biopsy has evolved into a routine method in Western European countries (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Usually, to keep the procedure of percutaneous needle biopsy as safe as possible, the procedure is under the guidance of different image modalities, such as computer tomography (CT), 12,14,15 ultrasound (US), [16][17][18] and magnetic resonance (MR). [19][20][21] Among these three major modalities, CT is used in most percutaneous needle biopsy procedures since it can balance the image quality and cost.…”
Section: Introductionmentioning
confidence: 99%